Franchisers, franchisees and success factors in international franchising - Hashim, Mohd Khairuddin; Ahmad, Shahrol Aman (Universiti Utara Malaysia Press, 2005)
International franchising plays an essential role in the global business system.International franchising has been considered as one of the most successful methods of entering international markets. Despite this fact,studies focusing on international franchising appear to have been not only limited but also neglected, particularly in the Malaysian context. The review of the literature suggests international franchising has attracted much theoretical as well as empirical attention from researchers as a serious field of study. Based on the authors' personal experiences and findings of previous studies, the present paper initiates an attempt to provide some insights into international franchising - focusing specifically on franchisers, franchisees and success factors in international franchising that have yet to be rigorously investigated - that could be both exploited and benefited by prospective franchisers, franchisees and future researchers.